Biofilms: Microbial Cities Wherein Flow Shapes Competition - Chew, Su Chuen (2017)
The phenotypic diversity in biofilms allows bacteria to adapt to changing environmental conditions. Stochastic gene expression and structural differentiation are believed to confer phenotypic diversity. However, two recent publications demonstrate how hydrodynamic flow and substrate topography can also alter the competitive outcomes of different bacterial phenotypes, increasing biofilm phenotypic variation.